Optimasi Desain Platformer Heater Dengan Penambahan Kapasitas Pengolahan Sweet Naphtha Pada Unit Platforming - Tun Sriana; Balqis Isya Candradi; Agus Setiyono (Universitas Proklamasi 45, 2026)
This research discusses the optimization of Platformer Heater design on PT platforming units.X with additional Sweet Naphtha processing capacity. The main objectives of optimization are toincrease energy efficiency, maintain reaction temperature stability at an optimal level, and overcomelimited heating capacity which has the potential to cause operational problems such as flameimpingement and overfiring. The research method includes Platformer Heater efficiency analysis andheat duty calculations carried out using Microsoft Excel. The operational data analyzed shows that theheating power requirement (Total Required Heater Duty) for the five interheaters has increasedsignificantly after the after conditions compared to the before conditions. The efficiency of eachinterheater is in the range of 70% to 72%, while the efficiency of the Platformer Heater is in the rangeof 70% to 80%. Even though efficiency between devices is relatively stable, this increase in heatingpower requirements indicates an increase in workload or changes in operational conditions that requirethese devices to use more power to continue functioning optimally. For example, interheater 2 requiresheating power of 139,967 Btu/hr in the before condition, which then increases to 221,614 Btu/hr in theafter condition. This confirms that changing conditions affect the amount of energy required for heating,so it is important to consider this in planning and operating the heating system so that efficiency andperformance are maintained. This study also emphasizes the importance of controlling Mean BeamLength and gas emissivity as key factors in increasing heater efficiency. Economic evaluation based onTotal Capital Investment and Operating Cost.